Defining the Israel’s offensive in Gaza: self-defence or war crimes? - Haruna, Abdulrashid Lawan; Eishan Jan, Mohammad Naqib (2014)
The Israel occupation of Palestinian territory has been an old aged occupation that frequently draws the attention of the United Nations and the International community. The recent rockets strike on Israel by the Hamas has led to the wanton killing of civilians and destruction of civilian property that deserve to be protected during hostilities. Israel considers the whole gamut of the offensives it has been launching on Gaza as a necessary measure to be taken to avert the situation. The direct attacks on civilians as well as civilian objects within the Gaza strip by the Israel forces have been portrayed as exercise of the right to self-defence. This paper examines the right of Israel to self-defence as envisaged under jus ad bellum aspect of international law and the obligation of belligerents (Israel) to observe jus in bello principles. The paper posits that Israel may exercise its right to self-defence which is regulated by the United Nations Charter but it is under an obligation to comply with the rules of international Humanitarian law (IHL). It further posits that the right of Israel to self-defence does not absolve it from the obligation to respect the basic principles of jus in bello. The paper concludes that the various breaches of IHL rules committed by Israel in its exercise of the right to self-defence amount to international crimes that are of serious concern. It is suggested that the Israel forces responsible for the violations of the Geneva Conventions and the Additional Protocols should be made to face the full wrath of the law.